Input from the grassroots level: Reflecting challenges and problems for VET professionals in Germany - Sebastian Anselmann; Stefan Harm; Uwe Faßhauer (International Journal for Research in Vocational Education and Training (IJRVET), 2022)
Context: Often, vocational education and training (VET) professionals are not systematically prepared for their demanding, mostly diverse and complex tasks. Professional development can be understood as an enlargement of competencies that arise as opportunities in daily work. This study, embedded in a funded research project, focuses on VET professionals and their professional development. The research question is as follows: What challenges and problems regarding their professional development, as well as possible solutions, are described by training professionals in VET in Germany? Approach: The goal of this study is to discover what challenges VET professionals face and how they cope with them. Accordingly, this research was formalised with the following components: (A) An explorative study with group discussions (N = 53 participants in six groups) and (B) result validation with German VET experts (N = 10). The data were recorded, transcribed and analysed using qualitative content analysis. Results: Using a theory-based category system, the group discussion results were summarised in 12 systematic, organisational- and individual-level statements. The statements indicated that despite the necessity of formal professional development in the area of further training, most VET professionals must still be able to profit from offers at or below the German Qualification Framework (DQR) level 5. Many VET professionals ultimately sought visible recognition of their activities or personal commitment with regard to pedagogical and company-economic functions. The 10 VET experts also evaluated the 12 statements as important. Conclusion: The results of this study show that there is a huge need for qualification and learning opportunities for VET professionals. The demand is mostly for modern, tried-and-tested concepts and central themes, such as action and competency orientation, practice and transfer orientation, individual and structural reflection, media competency and learning support in all formats and at all levels.
Keywords: 330; Continuing Vocational Education and Training; VET; Critical Analysis; Education and Training Opportunity; Qualitative Research; Relevance of Education and Training